ISLAMOPHOBIA IN UZMA JALALUDDIN’S HANA KHAN CARRIES ON (2021) - Amrullah, Aria Rafid; Sa’adah, Sufi ikrima (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
In the modern age of the West, Islamophobia emerges as a prevalent issue where Muslim minorities experience unjust treatment and violent actions. This issue affects many areas of Muslim culture, including contemporary literature. This study aims to reveal the depiction of Islamophobia in contemporary literature within Uzma Jalaluddin’s Hana Khan Carries On by employing the framework of Islamophobia as a manifestation of cultural racism. Results showed that the novel illustrates Islamophobia as a form of cultural racism, exemplified by characters addressing issues related to Muslim attire, exhibiting an anti-Arab perspective, and expressing disdain towards Islam and Muslim values.